Identifying Clusters Of Users In Twitter Dataset - Heidarian, Arash (2011)
This project propose an idea to cluster users in Twitter based on the keyword similarity and the connectivity among them. This task can be accomplished through 4 main steps, namely, Date Filtering, Tweet mining and keyword Extraction, Multi Clustering and Multi Conditional Cluster ranking.i